Visualisasi Konten Media Sosial terhadap Daya Tarik Wayang - Chandra, Vincent Patrick; Erdiansyah, Rezi (Kiwari, 2024)
Wayang is a cultural thing that has existed in Indonesia since Hinduism spread throughout the archipelago. However, with the development of the puppet era, many young people have abandoned it because puppets are considered an old-fashioned performance, so there is a need for social content tools to echo this puppet tradition. The aim of this research is to identify the impact of depicting social media content on the attractiveness of traditional culture (research on the preservation of wayang culture among young people). The research method used is a descriptive method with a quantitative approach, where the procedure for collecting information uses questionnaires. The research results prove that 1) the results of the t-experiment testing significance prove that there is a probability number of 0.000 ≤ 0.05. This figure can confirm that "Social Media Content Depictions influence the Attraction of Young People in Preserving Wayang"; 2) the results of the f experiment prove that the F number is 50,995 and the probability is 0.000. Because sig 0,000 < 0.05, it can be concluded that the elastic depiction of social content tools jointly influences the attraction of young people to preserving puppets; 3). As a result, researchers were able to conclude that the depiction of social media content has an important influence on attracting young people to preserve wayang traditions. This can be seen from the significance tests showing that there is a probability number of 0,000 ≤ 0.05. This figure can confirm that "Social Media Content Depictions influence the Attraction of Young People in Preserving Wayang". Wayang merupakan sesuatu kultur yang terdapat di Indonesia semenjak anutan Hindu sedang ter sebar diseluruh Nusantara. Tetapi bersamaan bertumbuhnya era wayang sendiri sudah banyak dibiarkan oleh golongan anak muda sebab wayang dianggap sesuatu pementasan yang terbelakang. Di era teknologi informasi saat ini, pelestarian budaya dapat menggunakan peran media sosial . Tujuan riset ini memeberikan gambaran Konten Sosial Media kepada Daya Tarik Pelanggengan Adat (Riset Pelanggengan Budaya Wayang Pada Anak Muda). Tata cara riset yang dipakai yakni tata cara deskriptif dengan pendekatan kuantitatif, yang mana tata cara pengumpulan informasi memakai penyebaran kuisioner. Hasil riset membuktikan kalau 1) hasil uji t pengetesan signifikansi membuktikan kalau ada angka kebolehjadian sebesar 0,000 ≤ 0,05. Angka itu bisa meyakinkan kalau “Penggambaran Konten Sosial Media mempengaruhi kepada Daya Tarik Anak Muda Melestarikan Wayang”; 2) hasil percobaan f membuktikan kalau didapat F jumlah sebesar 50.995 serta kebolehjadian sebesar 0,000. Sebab sig 0, 000 < 0,05, bisa disimpulkan kalau elastis Penggambaran Konten Sosial Alat dengan cara bersama-serupa mempengaruhi Daya Tarik Anak Muda Melestarikan Wayang ; 3) hasil pemastian membuktikan kalau membuktikan besarnya koefisien pemastian (Adjusted R2)= 0.336, maksudnya elastis Penggambaran Konten Sosial Media dengan cara bersama–sama pengaruhi variabel Daya Tarik Anak Muda Melestarikan Wayang sebesar 33.6% lebihnya sebesar 66.4%. Alhasil periset bisa merumuskan kalau Penggambaran konten sosial media mempengaruhi dengan cara penting kepada membuat daya tarik anak muda supaya melestarikan adat wayang, perihal itu nampak dari pengetesan signifikansi membuktikan kalau ada angka kebolehjadian sebesar 0, 000 ≤ 0,05. Angka itu bisa meyakinkan kalau “Penggambaran Konten Sosial Media mempengaruhi kepada Daya Tarik Anak Muda Melestarikan Wayang”.